Public Speaking Assistance for Madrasah Aliyah Students at Pondok Pesantren Alhamdulillah Geger Kedungadem Bojonegoro: Pendampingan Public Speaking Siswa-siswi Madrasah Aliyah di Pondok Pesantren Alhamdulillah Geger Kedungadem Bojonegoro - Ahmad Maujuhan Syah; Didik Kurniawan; Arina Iklil Nurul Ahlamiyah; Indah Puspita Sari; Nur Afifah; Muhammad Saiful Rohman (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
Many students want to develop in this modern era. the fact is that many students are not confident and skilled in the field of public speaking. Therefore, public speaking training is important to increase their self-confidence. The Asset Based Community Development method is used to carry out these activities with 5 stages of approach, namely Discovery, Dream, Design, Definition and Destiny. The results of this program are: Increased knowledge, understanding of the importance of public speaking skills, able to convey effective information, able to influence the public or audience, mastering ice breaking and being able to convey arguments and motivate the audience in a positive direction. During this activity, progress was seen very well. Because in this mentoring we don't just convey material but also change their way of thinking so that they become individuals who are confident in speaking in public and of course strengthened by consistent practice.